Has Western Germany a liberal market economy? - K.F. MAIER (PSL Quarterly Review, 2014)
The article takes a definite stand in favour of an economic policy based on a free market and price mechanism, which the author considers the most appropriate type of “economic order” for the solution of the two major problems facing post-war Germany, namely the development of exports and capital formation. The steps in this direction started in 1948 - which account, in the author’s opinion, for the surprising revival experienced by production and exports - have been, however, halted half-way. Thus, the author concludes that “Western Germany does not have a free market economy but something half-way towards such an economy; and this half-way position is not liberal, and is not intended to be so. What it is intended to be is a social market economy, and what it is in danger of becoming is a centrally directed economy”.